2013
DOI: 10.1179/2042618613y.0000000046
|View full text |Cite
|
Sign up to set email alerts
|

Validity of pain drawings for predicting psychological status outcome in patients with recurrent or chronic low back pain

Abstract: Objectives: To investigate the association between baseline pain drawings and future psychological status, and estimate the prognostic value of pain drawing assessment for predicting somatization, distress, and depression at one-year follow-up, in patients with recurrent or chronic low back pain (RCLBP). Methods: This was a multi-center prospective cohort study of 138 patients with RCLBP. Participating patients completed at baseline and one-year follow-up: a blank pain drawing; the Modified Somatic Perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We do not know if pain extent would be associated with dynamic outcomes such as wind-up, spatial/temporal summation, or conditioned pain modulation. Finally, we did not investigate the presence of psychological features that can be associated with higher pain extent [10] or abnormal pain drawings in individuals with chronic pain [24]. Nevertheless, a recent review did not support the assumption that unusual pain drawings predict the presence of a disturbed psychological state [25].…”
Section: Demographic and Clinical Data Of The Patientsmentioning
confidence: 91%
“…We do not know if pain extent would be associated with dynamic outcomes such as wind-up, spatial/temporal summation, or conditioned pain modulation. Finally, we did not investigate the presence of psychological features that can be associated with higher pain extent [10] or abnormal pain drawings in individuals with chronic pain [24]. Nevertheless, a recent review did not support the assumption that unusual pain drawings predict the presence of a disturbed psychological state [25].…”
Section: Demographic and Clinical Data Of The Patientsmentioning
confidence: 91%
“…No meta-analysis was performed and only English-language articles were included, raising the risk of publication bias. Finally, it is important to emphasize that the database search in Carnes’ review was performed in the first three months of 2003 and subsequently, different authors have expressed contrasting opinion about on the influence of psychosocial factors on PD in LBP 15 , 16 , 17 , 18 ) . In particular, Abbott 16 ) and Turk 18 ) have argued that for some patients, the drawing might be influenced by psychosomatic disorders, and could be used to alert medical and health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…These data agree with previous studies, in which patients with chronic pain in several body regions at the same time had anxiety levels that were considered pathological compared with patients having more localized pain. Moreover, they had greater depression and feelings of distress (Abbott, Foster, Hamilton, Ravenwood, & Tan, 2015; Muñoz-García, Lopez-Uralde-Villanueva, Beltrán-Alacreu, La Touche, & Fernández-Carnero, 2016). Evidence has shown that CWP not only correlates with psychological variables but also correlates with somatosensory variables, such as the severity of symptoms or mechanical hyperalgesia (Ferrer-Peña, Muñoz-García, Calvo-Lobo, & Fernández-Carnero, 2018).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%